Efek Pemberian Daging Buah Durian (Durio Zibethinus) terhadap Fungsi Ginjal Berdasarkan Ureum dan Kreatinin pada Tikus Putih Jantan Galur Wistar (Rattus Norvegicus L.) - Raja Iqbal Alamsyah; Robitah Asfur (The Journal General Health and Pharmaceutical Sciences Research, 2024)
Examination of serum urea and creatinine levels is an important indicator in assessing the physiological function of the kidneys. Consumption of durian, which is rich in potassium, may increase the risk of hyperkalemia, especially in patients with chronic kidney disorders. One of the popular durian species in Indonesia is Durio zibethinus, which is native to the forests of Sumatra, Malaysia and Kalimantan. Its complex nutritional content may affect kidney function if consumed in excess. This study aims to evaluate the effect of durian (Durio zibethinus) pulp administration on changes in kidney function, especially urea and creatinine levels, in male Wistar white rats (Rattus norvegicus L.). This study used a true experimental design with a posttest-only design with control group design. A total of 24 rats were divided into four groups: negative control, positive control, and two treatment groups with durian fruit pulp in graded doses for 28 days. Measurement of ureum and creatinine levels was performed, and data analysis used One-Way ANOVA test with Bonferroni and Kruskal-Wallis post hoc. Durian administration in graded doses in the treatment group showed a significant effect on increasing ureum and creatinine levels compared to the negative control group (p < 0.05). However, there were no significant differences between treatment groups (P1, P2, and P3) (p> 0.05). Administration of durian fruit pulp at graded doses has a significant effect on increasing ureum and creatinine levels, indicating changes in kidney function in Wistar rats. This finding underscores the importance of regulating durian consumption, especially for individuals at risk of renal impairment.